2015
DOI: 10.1002/jsfa.7068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature during grain filling on gluten viscoelastic properties and gluten protein composition

Abstract: Constant low temperature, even as low as 13 °C, had no negative effects on gluten quality. The observed variation in Rmax related to temperature could be explained more by %UPP than by changes in the proportions of HMW-GS or other gluten proteins. The four cultivars responded differently to temperature, as gluten from Berserk was stronger and more stable over a wide range of temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
(109 reference statements)
0
20
0
Order By: Relevance
“…Naeem et al (2012) showed that polymerization of glutenin subunits occurs late in wheat maturation. Koga et al (2015) and Blumenthal et al (1995) showed that cultivars differed in the impact of temperature variation on dough strength. Koga et al (2015) found that high temperatures changed the glutenin/gliadin ratios and had a negative impact on tolerance to mixing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naeem et al (2012) showed that polymerization of glutenin subunits occurs late in wheat maturation. Koga et al (2015) and Blumenthal et al (1995) showed that cultivars differed in the impact of temperature variation on dough strength. Koga et al (2015) found that high temperatures changed the glutenin/gliadin ratios and had a negative impact on tolerance to mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of individual glutenin genes and the assembly of glutenin polymers is affected by the stage of seed development and the environmental conditions during seed development (Blumenthal et al, 1995;Jia et al, 2012;Naeem et al, 2012;Giuliani et al, 2015;Koga et al, 2015). Expression of individual glutenin genes and the assembly of glutenin polymers is affected by the stage of seed development and the environmental conditions during seed development (Blumenthal et al, 1995;Jia et al, 2012;Naeem et al, 2012;Giuliani et al, 2015;Koga et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, longer green leaf duration after heading was also associated with lower gluten strength and reduced loaf volume (Blake et al., ). Several studies have shown that polymerization of individual gluten proteins occurs late in seed development and is impeded by high temperatures (Blumenthal, Bekes, Gras, Barlow, & Wrigley, ; Giuliani et al., ; Jia, Dai, & He, ; Koga, Bocker, Moldestad, Tosi, & Shewry, ; Naeem, Paulon, Irmak, & MacRitchie, ). These studies suggest an explanation for the reduced gluten strength of cultivars with extended green leaf duration after heading.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous matrix formed from gluten proteins confers viscoelastic properties to the dough, which can be processed into products of various shapes. The viscoelastic properties are strongly related to the molecular weight of the glutenin (Guo et al, 2015;Koga et al, 2016). For example, dough with high viscoelasticity has been shown to have higher proportions of high molar mass glutenin polymers (Field, Shewry & Miflin, 1983).…”
Section: Gluten Proteinsmentioning
confidence: 99%